Selectivity of certain biorational insecticides against chrysopid (Mallada boninensis) and coccinellid (Serangium parcesetosum) predators - RAO, C N; SHIVANKAR, V J (The Indian Journal of Agricultural Sciences, 2012)
The selectivity of nine biorational insecticides, viz spinosad, abamectin, novaluron, petroleum spray oil, neem oil, azadirachtin, sweet flag extract, Bacillus thuringiensis, Verticillium lecanii and dimethoate (as standard) was evaluated against the chrysopid (Mallada boninensis Okamoto) (Neuroptera : Chrysopidae) and Serangium parcesetosum Sicard (Coleoptera: Coccinellidae), the predominant predators of the soft bodied insect pests of Nagpur mandarin (Citrus reticulata Blanco) in the laboratory at National Research Centre for Citrus, Nagpur, during 2007 and 2008. Of the biorational insecticides tested, rhizome extract of A. calamus @ 3.4% was found safer to M. boninensis with regard to larval mortality (25.8%) being lowest and egg hatchability (94.0%),% pupation (90.9%),% adult emergence (82.4%), adult longevity (40.5 days) and fecundity (127.2 eggs/female) being highest. Similarly, rhizome extract of A. calamus @ 3.4% was also found safer to S. parcesetosum with regard to larval mortality (19.1%) being lowest and% pupation (89.3%) and% adult emergence (81.5%) being highest than other bio-rational insecticides tested.